Impak limpahan pembandaran ke atas kampung pinggir bandar di wilayah metropolitan - Amir, Anuar (2006)
Village settlements located in urban fringes at metropolitan regions are being hemmed by the urban overspill. Some undergo identity changes and dissolved into intensive planned development trends. Studies overseas have identified various physical and non-physical effects due to the urban overspill but the impacts focused are general, basically on land uses or the development of fringe areas as a whole. This research is focused specifially more on impacts experienced by suburban villages population due to the urban overspill phenomenon. This is important in developing planning parameters for village settlements in the suburb areas, particularly involving resettlement programmes, upgrading or even for the redevelopment of the area. The study method uses urban influence indices to determine impact indicators within the physical, sosioeconomic and sociocultural aspects. Sixteen suburban villages were surveyed, involving 367 households and 84 impact variables. Ranking and correlation analysis on the influences of distance from urban boundary, identified 16 significant impact indicators. Chi-square tests on the indicators found two indicators i.e a) decrease in numbers of kampung house type, and b) decrease in house ownership, occurred in all impact zones. More detail findings indicated that urban overspill gives more impacts on non-physical rather than physical aspects. The level of housing quality and physical facilities in the study area are low and these have affected the quality of life of the population. The distance of settlements from the urban boundary was found to be the main determinant of the impacts. The urban overspill afforded more positive effects on physical aspects such as good social facilities, compared to socioeconomic or sociocultural components. Urban overspill also increased social problems such as crimes, thefts, and drug addictions in certain settlements. To ensure that rural settlements near big towns are not continuously under development pressure, a more comprehensive rural development planning policy is needed. The regionalisation of rural settlements is a planning parameter toward enhancing rural quality of life through more dynamic sustainable development. Urban overspill can be controlled by creating new planning regions combining typological characteristics of the rural-urban as intermediate development areas. This region can create wider potentials for suburban development replacing the rigid urban boundary. The overall findings in this research indicated the weaknesses in urban planning with regards to integrating non-physical and physical aspects to promote better living. Focus in urban planning should be reviewed towards a more comprehensive-based development strategy in relation to a wider needs of regional planning. This may evoke towards a more holistic planning approach in the field of urban and regional planning